A wearable photoplethysmography sensor for non-invasive equine heart rate monitoring - Morgan Miller; Richard Byfield; Marci Crosby; Paul Schiltz; Philip J. Johnson; Jian Lin (Smart Agricultural Technology, 2023)
In recent years, advancement in biomedical sensors has led to increasingly accurate and accessible biological vital sign collection in nontraditional and noncontrolled application domains. Despite much progress, the implementation within the veterinary medicine field is still limited, which, in part, is due to a lack of rapid, robust, and easy-to-use sensors. To tackle this challenge this work presents a compact and wearable photoplethysmography (PPG) sensor for monitoring equine heart rates (HRs) from the ventral midline near the base of the tail. The PPG waveforms were robustly collected from a group of 50 equine subjects with various age, sex, and breed and then used for HR calculation. The system achieved an accuracy of 94% for HR calculation from the subjects at rest compared to the ground truth HRs acquired from the same subjects by a stethoscope. Statistical analysis on the collected data was conducted to further investigate the robustness of the HR calculations in different age, sex, and breed demographics. This work demonstrates that the PPG-based sensor for HR monitoring shows great potential of being a complementary tool in veterinary medicine for promoting furtherance of the animal health.